Two New Species of Collybiopsis (Agaricales, Omphalotaceae) from Mudeungsan National Park in Korea - Minseo Cho; Yeonjae Yoo; Sang Hyun Lee; Dae Young Kwon; Changmu Kim; Young Min Lee; Sun Lul Kwon; Jae-Jin Kim (Mycobiology)
Collybiopsis (Agaricales, Omphalotaceae) is a saprobic mushroom-forming genus characterized by gymnopoid, omphaloid, and pleurotoid basidiome, and ellipsoid to cylindrical basidiospores. Currently, 66 species are classified as the genus Collybiopsis through continuous taxonomic validations to resolve taxonomic confusions caused by morphological similarities with other genera, such as Marasmiellus and Gymnopus. In Korea, 16 Collybiopsis species have been recently identified, but there are still many undiscovered species. In this study, four Collybiopsis specimens were collected from Mudeungsan National Park in July from 2021 to 2022. They were identified as two new species through morphological, molecular, and multi-marker phylogenetic analyses based on nuclear ribosomal internal transcribed spacer (ITS) and nuclear large subunit ribosomal DNA (nLSU) regions. Detailed morphological descriptions and a phylogenetic tree are provided to suggest these species as C. albida sp. nov. and C. pini sp. nov.